Role of mitophagy in the neurodegenerative diseases and its pharmacological advances: A review - Wang, Qixia; Xue, Haoyuan; Yue, Yundi; Hao, Shiqi; Huang, Shu-Hong; Zhang, Zhaoqiang (Frontiers in Molecular Neuroscience, 2022)
Neurodegenerative diseases are a class of incurable and debilitating diseases characterized by progressive degeneration and death of cells in the central nervous system. They have multiple underlying mechanisms; however, they all share common degenerative features, such as mitochondrial dysfunction. According to recent studies, neurodegenerative diseases are associated with the accumulation of dysfunctional mitochondria. Selective autophagy of mitochondria, called mitophagy, can specifically degrade excess or dysfunctional mitochondria within cells. In this review, we highlight recent findings on the role of mitophagy in neurodegenerative disorders. Multiple studies were collected, including those related to the importance of mitochondria, the mechanism of mitophagy in protecting mitochondrial health, and canonical and non-canonical pathways in mitophagy. This review elucidated the important function of mitophagy in neurodegenerative diseases, discussed the research progress of mitophagy in neurodegenerative diseases, and summarized the role of mitophagy-related proteins in neurological diseases. In addition, we also highlight pharmacological advances in neurodegeneration.